In our own hands essays in deaf history, 1780-1970 - Greenwald, Brian H.; Murray de Melgum, Joseph J. (Gallaudet University Press, 2016)
"This collection of new research examines the development of deaf people's autonomy and citizenship discourses as they sought access to full citizenship rights in local and national settings. Covering the period of 1780-1970, the essays in this collection explore deaf peoples' claims to autonomy in their personal, religious, social, and organizational lives and make the case that deaf Americans sought to engage, claim, and protect deaf autonomy and citizenship in the face of rising nativism and eugenic currents of the late nineteenth and early twentieth century. These essays reveal how deaf people used their agency to engage in vigorous debates about issues that constantly tested the values of deaf people as Americans. The debates overlapped with social trends and spilled out into particular physical and social spaces such as clubs and churches, as well as within families. These previously unexplored areas in Deaf history intersect with important subthemes in American history, such as Southern history, religious history, and Western history. The contributors demonstrate that as deaf people pushed for their rights as citizens, they met with resistance from hearing people, and the results of their efforts were decidedly mixed. These works reinforce the Deaf community's longstanding desire to be part of the state...that is, to be first-class citizens. In Our Own Hands contributes to an increased understanding of the struggle for citizenship and expands our current understanding of race, gender, religion, and other trends in Deaf history"...